Code Switching and Code Mixing in the Interaction of the Mandar Community in Sumbawa Regency - Suparman, Suparman (International Seminar on Austronesian Languages and Literature; Vol 9 No 1 (2021): PROCEEDINGS International Seminar on Austronesian Languages and Literature IX (ISALL IX), 2021)
The speakers of Mandar language as a minority speaker, whose live in the middle majority of Sumbawa language speakers. They are certainly influenced of language majority surrounding of them. Therefore, this study is aimed to find out is in their utterance or daily communication the Mandar language speakers has occurred a code switching and code mixing. If in the Mandar language has occured a code switching and code mixing what the form of code switching was happened. The method used in this study is a listening method. The data has been obtained analyzed by using descriptive method. The result of this research is in the utterance or daily communication of Mandar language speaker has happened a code switching and code mixing.  They are used Mandar language fully when they communication with their comunity and Sumbawa speakers in Sumbawa regency. The code switching and code mixing phenomenon in communities of Mandar language speaker in Sumbawa regency is a their strategy to retention their language